Lesion size determines diagnostic yield of EUS-FNA with onsite cytopathologic evaluation for upper gastrointestinal subepithelial lesions - Attila, Tan; Aydın, Özlem (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: The aim of this study was to determine the diagnostic yield and factors influencing the diagnostic yield of endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) for upper gastrointestinal (GI) subepithelial lesions (SELs) with rapid onsite cytopathologic evaluation. Materials and Methods: This is a single-center, retrospective study. Results: Among 22 patients who underwent EUS-FNA, a cytopathological diagnosis was reached in 16 (72.7%) patients. The EUS-FNA results were as follows: seven GISTs (31.8%), six leiomyomas (27.2%), four non-diagnostics (18%), two duplication cysts (9%), two spindle cell tumor (9%), and one ectopic pancreas (4.5%). The long-axis size was >20 mm in 12 patients (average size: 31.3 ±9.3 mm) and <20 mm (average size: 16.6 ±2.5 mm) in 10 patients. Diagnostic accuracy of EUS-FNA from lesions <20 mm was 50% (5/10 lesions), and of lesions >20 mm was 91.6% (11/12 lesions) (Fisher’s exact test; p=0.028). Six patients underwent surgical resection. Surgical pathology results of five lesions (four GIST, one leiomyoma) were consistent with cytopathology results (83.3%). Conclusion: The diagnostic yield of EUS-FNA of the upper GI SELs with an onsite cytopathologic interpretation was 72.7%. Lesion size <2 cm significantly reduces the diagnostic yield of EUS-FNA for the upper GI SELs. Cite this article as: Attila T, Aydın Ö. Lesion size determines diagnostic yield of EUS-FNA with onsite cytopathologic evaluation for upper gastrointestinal subepithelial lesions. Turk J Gastroenterol 2018; 29: 436-41.